Assessing progress towards universal health coverage in Cambodia: Evidence using survey data from 2009 to 2019. (March 2023) - Kaiser, Andrea Hannah; Okorafor, Okore; Ekman, Björn; Chhim, Srean; Yem, Sokunthea; Sundewall, Jesper
Abstract: Over the past decades, many low- and middle-income countries have implemented health financing and system reforms to progress towards universal health coverage (UHC). In the case of Cambodia, out-of-pocket expenditure (OOPE) remains the main source of current health expenditure after several decades of reform, exposing households to financial risks when accessing healthcare and violating UHC's key tenet of financial protection. We use pre-pandemic data from the nationally representative Cambodia Socio-Economic Surveys of 2009 to 2019 to assess progress in financial protection to evaluate the reforms and obtain internationally comparable estimates. We find that following strong improvements in financial protection between 2009 and 2017, there was a reversal in the trend thereafter. The OOPE budget share rose, and the incidence of catastrophic spending and impoverishment increased in nearly all geographical and socioeconomic strata. For example, 17.7% of households experienced catastrophic health expenditure in 2019 at the threshold of 10% of total household consumption expenditure, and 3.9% of households were pushed into poverty by OOPE. The distribution of all financial protection indicators varied strongly across socioeconomic and geographical strata in all years. Fundamentally, the demonstrated trend reversal may jeopardize Cambodia's ability to progress towards UHC. To improve financial protection in the short term, there is a need to address the burden created by OOPE through targeted interventions to household groups that are most affected. In the medium term, our findings emphasize the importance of expanding health pre-payment schemes to currently uncovered vulnerable groups, specifically the near-poor. The government also needs to consider extending the scope of services covered and the range of providers to include the private sector under these schemes to reduce reliance on OOPE. Highlights: From 2009 to 2017, Cambodia made substantial improvements in financial protection. Increasing incidence of catastrophic and impoverishing spending from 2017 to 2019. Trend reversal caused by faster growth of out-of-pocket spending than consumption. Targeted interventions are needed to reduce the burden of out-of-pocket spending. Extending pre-payment mechanisms to uncovered vulnerable groups will be critical.